Response to a New Wave in Digital Marketing: Does Beauty Blogger Involvement The Most Influencing Factor in Halal Cosmetic Purchase Intention - Telisiah Putri Utami Putri; Sri Bramantoro Abdinagoro (International Journal of Supply Chain Management, 2018)
Cosmetics market in Indonesia indicated a significant change in the last 5 years where market gets filled with halal cosmetic products, along with the increasing demand for halal cosmetic, cosmetic manufacturer should be able to answer the needs of today's consumers. Efforts to continually address consumer needs and success in the market trigger cosmetic manufacturer to take into account factors suspected having strong influence to stimulate consumer purchase intention towards halal cosmetic. Digital marketing is becoming a new phenomenon, beauty blogger involvement through social media and youtube brings out a new marketing way, beauty blogger involvement becomes important thing to cosmetic brand due to bloggers review attract consumer respond whether to like and keen to try product or even reluctant to it. This study aims to conduct a preliminary study of factors which predicted has strong influence to stimulate purchase intention towards halal cosmetic. Beauty blogger involvement via social media and Youtube, Arabic brand name, religiosity and halal logo, those are some antecedents choosen to be checked whether significantly influence Purchase Intention in halal cosmetic. This study will take respondents women from age 20 up to 40 years old, active internet and social media users, using mass-market cosmetic brand, they are Jakartas residents, the survey will be conducted via on-line survey. The result of this study is expected to be a preliminary study to analyse the most influencing factor in halal cosmetic purchase intention